Book review: Bernardi, F. and Ballarino, G., editors, 2016: Education, Occupation and Social Origin. A Comparative Analysis of the Transmission of Socio-Economic Inequalities. (July 2018) - Segura, Claudia Yvonne Linan
Bernardi, F. and Ballarino, G., editors, 2016: Education, Occupation and Social Origin. A Comparative Analysis of the Transmission of Socio-Economic Inequalities . Cheltenham: Edward Elgar Publishing Limited. 304 pp. £85.00 (Paperback), £76.50 (eBook). ISBN: 9781785360442 (Paperback), 9781785360459 (eBook).